EFFECT OF SOME DISPERSING AUXILIARIES ON NANOSILICA DISPERSION INTO PASSIVE CHROME TRIVALENT SOLUTION - Nam, Truong Thi; Huong Thuy, Hoang Thi; Hung, Dao Phi; Thang, Le Ba; Cam Ha, Nguyen Thi (Vietnam Journal of Science and Technology, 2016)
In this paper, the dispersion of nanosilica in conversion solution trivalent chromium using variety of dispersion aids namely: SDS, PVP, AE-7, OP-10 and epomin. The results showed that the nanosilica could disperse in conversion solution in low pH (pH = 1.5). The solution containing nanosilica was uniform, having no agglomeration with SDS, PVP and AE-7 after 7-day preparation. The results of zeta potential and size distribution illustrated that AE-7 was the most effective for nanosilica dispersion in passive solution trivalent chromium with medium size of nanosilica in C2-nanosilica solution using AE-7 equal 60 nm. However, there was a much diffirence size between the size of nanosilica in passive solution and initial nanosilica. As a result, nanosilica could disperse in passive solution at low pH with AE-7 but this was not effective enough to held dispersed solution in stable state.